2013
DOI: 10.7567/apex.6.095502
|View full text |Cite
|
Sign up to set email alerts
|

Highly Uniform Electroluminescence from 150 and 200 mm GaN-on-Si-Based Blue Light-Emitting Diode Wafers

Abstract: We report on the on-wafer device characteristics of 150 and 200 mm GaN-on-Si-based blue LED wafers grown by metalorganic chemical vapor deposition on Si(111) substrates with electroluminescence at 447 nm. Excellent uniformity was achieved with standard deviations of 3.9% for the electroluminescence intensity, 0.6–0.8% for the peak wavelength and 1.3% for the forward voltage. The high uniformity confirms the viability of the GaN-on-Si technology on large-diameter substrates for next-generation LED manufacturing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…More interestingly, the emission efficiency of the white LED emitter, which was fabricated from the epi-wafer of InGaN-based LEDs on a Si substrate, was successfully increased to 110 lm/W. To the best of the authors' knowledge, this white LEDs emitter with InGaNbased LEDs on a Si substrate is the first to reach an efficiency of 110 lm/W [37]- [41]. We believe that the efficiency of InGaN-based LEDs on Si substrate can be further increased by improving the technique of epitaxial growth and the chip process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More interestingly, the emission efficiency of the white LED emitter, which was fabricated from the epi-wafer of InGaN-based LEDs on a Si substrate, was successfully increased to 110 lm/W. To the best of the authors' knowledge, this white LEDs emitter with InGaNbased LEDs on a Si substrate is the first to reach an efficiency of 110 lm/W [37]- [41]. We believe that the efficiency of InGaN-based LEDs on Si substrate can be further increased by improving the technique of epitaxial growth and the chip process.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, many other growth techniques have been used; they include a GaN-free buffer layer [24], [25], a strained layer of AlN/GaN superlattices (SLs) [26], a single AlN buffer layer or multiple layers of AlN/GaN [27]- [29], an AlGaN buffer layer with an Al gradient [30], a patterned Si substrate [31], [32], selective growth [33], [34], a porous Si substrate [35], and Si on an insulator as a compliant substrate [36]. Although the successful growth of crack-free and highquality GaN epilayer on Si has been reported, the white-light LEDs performance of InGaN-based LEDs on Si remains very poor and no major breakthrough in their emission efficiency or light output power has been made [37]- [41].…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, it should be of little surprise that LED yields struggle to exceed 90%. Wafer growth techniques to specifically address these challenges have been applied [4]. However, binning and selection of known good die remains best practice within the LED industry.…”
Section: Yield Consideration Of Iled Displaysmentioning
confidence: 99%
“…This is to be the standard for UHD applications and is almost 90% larger that the sRGB space. Recently work with quantum dots has shown that their range of wavelengths and narrow emission spectra (relative to traditional phosphors) [5] [4] can provide superior color performance. Inherently, LEDs have relatively narrow emission spectral -approx.…”
Section: Improved Color Gamutmentioning
confidence: 99%
“…Si substrates are one of the ideal substrates owing to their thermal and electrical properties, which would induce in-plane tensile stress to compensate the compressive stress in the InGaN=GaN MQW structures. 28,29) With the improvement of wafer-bonding techniques, the efficiency of the material integration of thinfilm GaN with Si substrates can compete with that of LEDs grown on a patterned sapphire substrate. [30][31][32][33] In this study, the InGaN=GaN MQW structures were grown on 2-in.…”
mentioning
confidence: 99%